A Synthetic Spring‐Neap Tidal Cycle for Long‐Term Morphodynamic Models. Issue 3 (26th February 2023) - Schrijvershof, R. A.; van Maren, D. S.; Torfs, P. J. J. F.; Hoitink, A. J. F.
Abstract: Existing tidal input reduction approaches applied in accelerated morphodynamic simulations aim to capture the dominant tidal forces in a single or double representative tidal cycle, often referred to as a "morphological tide." These strongly simplified tidal signals fail to represent the tidal extremes and hence poorly allow to represent hydrodynamics in the intertidal areas. Here, a generic method is developed to construct a synthetic spring‐neap tidal cycle that (a) represents the original signal; (b) is exactly periodic; and (c) is derived directly from tidal time series or harmonic constituents. The starting point is a fortnightly modulation of the semidiurnal tide to represent spring‐neap variations, while conserving periodicity. Diurnal tides and higher harmonics of the semidiurnal tide are included to represent the asymmetry of the tide. The amplitudes and phases of the synthetic signal are then fitted to histograms of water levels and water level gradients derived from the original sea surface elevation time series. A depth‐averaged model of the Ems estuary (The Netherlands) demonstrates the effects of alternative tidal input reduction techniques. Adopting the new approach, the along‐estuary variation in tidal wave shape is well‐represented, leading to an improved representation of extreme tidal conditions. Especially the more realistic representation of intertidal dynamics improves the overall hydrodynamics and residual sand transport patterns, approaching nonschematized tidal dynamics. Plain Language Summary: The daily emerging and inundation of tidal flats occurs much faster than the emerging or drowning of tidal flats by sedimentation or erosion (hours vs. years, respectively). To efficiently simulate years of erosion and deposition, an acceleration factor is applied to models that simulate the long‐term bed level developments. Tidal information used to force these models requires an input reduction technique that copes with the fact that successive spring‐neap cycles are never identical. In this paper, a tidal input reduction method is developed that yields a synthetic, periodic tidal signal representing the amplitude and asymmetry variation present in a multiyear tidal signal. These variations are not captured well in existing, more limited, approaches for tidal input reduction, likely restricting their application for longer timescales, because neglecting these variations can cause errors to accumulate in the course of a simulation. Results from a numerical model forced with the synthetic signal shows that, compared to existing approaches, particularly the intertidal dynamics and residual sand transports better represent the multiscale tidal conditions. Therefore, the new tidal input reduction method should improve the channel‐shoal exchange in long‐term estuarine models, presumably allowing for a more realistic assessment of erosion and deposition in these areas. Key Points: A new approach to devise periodic tidal boundary conditions for long‐term morphodynamic simulations is developed The new method better represents tidal water level dynamics, bed shear stress, and residual sand transport Including spring‐neap variations in the tidal input reduction approach particularly improves hydrodynamics in intertidal areas